The analgesic activity of Bestatin as a potent APN inhibitor - Jia, Mei-Rong; Wei, Tao; Xu, Wen-Fang (Frontiers in Neuroscience, 2010)
Bestatin, a small molecular weight dipeptide, is a potent inhibitor of various aminopeptidases as well as LTA4 hydrolase. Various physiological functions of Bestatin have been identified, viz.: (1) an immunomodifier for enhancing the proliferation of normal human bone marrow granulocyte–macrophage progenitor cells to form CFU-GM colonies; Bestatin exerts a direct stimulating effect on lymphocytes via its fixation on the cell surface and an indirect effect on monocytes via aminopeptidase B inhibition of tuftsin catabolism; (2) an immunorestorator and curative or preventive agent for spontaneous tumor; Bestatin alone or its combination with chemicals can prolongate the disease-free interval and survival period in adult acute or chronic leukemia, therefore, it was primarily marketed in 1987 in Japan as an anticancer drug and servers as the only marketed inhibitor of Aminopeptidase N (APN/CD13) to cure leukemia to date; (3) a pan-hematopoietic stimulator and restorator; Bestatin promotes granulocytopoiesis and thrombocytopoiesis in vitro and restores them in myelo-hypoplastic men; (4) an inhibitor of several natural opioid peptides. Based on the knowledge that APN can cleave several bioactive neuropeptides such as Met-enkaphalins, Leu-enkaphalins, β-Endorphin, and so on, the antiaminopeptidase action of Bestatin also allows it to protect endopeptides against their catabolism, exhibiting analgesic activity. Although many scientific studies and great accomplishments have been achieved in this field, a large amount of problems are unsolved. This article reviews the promising results obtained for future development of the analgesic activity of Bestatin that can be of vital interest in a number of severe and chronic pain syndromes.